Komunikasi Pemasaran Desa Wisata Sendang Kun Gerit Gemolong Sragen Dalam Meningkatkan Kunjungan Wisatawan - Sixnata, Rulhy Adhy; Suryo, Herning; Sihabuddin, Sihabuddin (Solidaritas, 2025)
Advances in communication and technology due to globalization have presented opportunitiesand challenges for the tourism sector in Indonesia. One of the developing destinations isSendang Kun Gerit, a natural bathing-based tourist attraction in Sragen Regency. Thisresearch aims to describe the marketing communication strategies implemented to increasethe number of visitors. This research uses a qualitative descriptive method with data collectiontechniques through interviews, observation and documentation. The research results show thatthe marketing communications implemented include online marketing via social media, publicrelations, personal selling, and sales promotions. The strategy contributed to an increase inthe number of tourists, especially during the holiday season. It is proven that every month thenumber of visitors increases and the busiest occurs in December 2024, reaching 35,231 peoplevisiting Sendang Kun Gerit.Keywords: Marketing Communications, tourism, Sendang Kun Gerit